Vaccination against SARS-CoV-2 protects from morbidity, mortality and sequelae from COVID19 in patients with cancer. (August 2022) - Pinato, David J.; Ferrante, Daniela; Aguilar-Company, Juan; Bower, Mark; Salazar, Ramon; Mirallas, Oriol; Sureda, Anna; Bertuzzi, Alexia; Brunet, Joan; Lambertini, Matteo; Maluquer, Clara; Pedrazzoli, Paolo; et al.
Abstract: Background: Although SARS-CoV-2 vaccines immunogenicity in patients with cancer has been investigated, whether they can significantly improve the severity of COVID-19 in this specific population is undefined. Methods: Capitalizing on OnCovid (NCT04393974) registry data we reported COVID-19 mortality and proxies of COVID-19 morbidity, including post-COVID-19 outcomes, according to the vaccination status of the included patients. Results: 2090 eligible patients diagnosed with COVID-19 between 02/2020 and 11/2021 were included, of whom 1930 (92.3%) unvaccinated, 91 (4.4%) fully vaccinated and 69 (3.3%) partially vaccinated. With the exception of a higher prevalence of patients from the UK (p = 0.0003) and receiving systemic anticancer therapy at COVID-19 diagnosis (p = 0.0082) among fully vaccinated patients, no demographics/oncological features were associated with vaccination status. The 14-days case fatality rate (CFR) (5.5% vs 20.7%, p = 0.0004) and the 28-days CFR (13.2% vs 27.4%, p = 0.0028) demonstrated a significant improvement for fully vaccinated patients in comparison with unvaccinated patients. The receipt of prior full vaccination was also associated with reduced symptomatic COVID-19 (79.1% vs 88.5%, p = 0.0070), need of COVID-19 oriented therapy (34.9% vs 63.2%, p < 0.0001), complications from COVID-19 (28.6% vs 39.4%, p = 0.0379), hospitalizations due to COVID-19 (42.2% vs 52.5%, p = 0.0007) and oxygen therapy requirement (35.7% vs 52%, p = 0.0036). Following Inverse Probability Treatment Weighting (IPTW) procedure no statistically significant difference according to the vaccination status was confirmed; however, all COVID-19 related outcomes were concordantly in favour of full vaccination. Among the 1228 (58.8%) patients who underwent a formal reassessment at participating centres after COVID-19 resolution, fully vaccinated patients experienced less sequelae than unvaccinated patients (6.7% vs 17.2%, p = 0.0320). Conclusions: This analysis provides initial evidence in support of the beneficial effect of SARS-CoV-2 vaccines against morbidity and mortality from COVID-19 in patients with cancer. Highlights: Immunogenicity of SARS-CoV-2 vaccines in patients with cancer has been investigated. There is a need for evidence of SARS-CoV-2 vaccines' efficacy from large populations. In this analysis, vaccinated patients experienced improved COVID-19 outcomes. SARS-CoV-2 vaccines are effective in reducing severe COVID-19 in patients with cancer.